Hubungan Dukungan Suami dan Peran Petugas Kesehatan Terhadap Pemilihan Alat Kontrasepsi Jangka Panjang pada Wanita Usia Subur di Polindes Kefa Utara - Avelina Paskalia Gusman; Maria Magdalena Theofila Duka; Brigita Dina Manek; Nabilah Nurul Ilma (Lembaga Pengembangan Kinerja Dosen, 2025)
Contraception is used to control population growth and ensure the availability of natural resources, thereby maintaining the quality of human life. Contraceptive methods can be categorized into two types: long-term contraceptive methods (LTCMs), such as intrauterine devices (IUDs), implants, female sterilization (tubal ligation or MOW), and male sterilization (vasectomy or MOP); and short-term contraceptive methods (non-LTCMs), such as condoms, injections, and oral contraceptive pills. The aim of this study is to examine and explain the relationship between spousal support and the role of healthcare workers in the selection of long-term contraceptive methods among women of reproductive age in the working area of the Kefa Utara Village Maternity Post, North Central Timor Regency. This research is quantitative with a cross sectional approach. The sampling technique used accidental sampling with a total of 106 WUS respondents. Data analysis using Chi Square test analysis. The results showed that women of reproductive age who did not get husband's support were higher (57.50%) than those who got husband's support (42.50%). Chi-Square test showed a significant relationship between husband's support and the selection of LTCMS (p < 0.05) with an Odds Ratio (OR) value of 2.690. In addition, health workers who played a role in the selection of LTCMS were greater (67.90%) than health workers who did not play a role (32.10%). The Chi Square test results also showed a significant relationship between the role of health workers and the selection of LTCMS (p < 0.05) with an 0R value of 3.733.